2012
DOI: 10.1007/s11060-012-0962-9
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral nervous system immune mediated demyelinating disease after allogeneic hemopoietic stem cell transplantation for hematologic disease

Abstract: Immune mediated demyelinating disease (IMDD) after allogeneic hemopoietic stem cell transplant (HSCT) is rare and its etiology unclear. In this retrospective study, we identified patients who underwent HSCT between January 1992 and December 2010 and had IMDD post transplant. A total of 1,484 patients received HSCT and 7 (0.5 %) suffered from IMDD; five were men, and the median age was 54 years (range, 29-64 years). HSCT treated acute myeloid leukemia (n = 5), myelodysplastic syndrome (n = 1), and Waldenström m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
64
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 18 publications
3
64
1
1
Order By: Relevance
“…6,7 In these cases, treatment with steroids and immunosuppression led to neurological improvement and stabilisation in 3 of a series of 4 cases. 7 A recent study from Memorial Sloan Kettering 8 showed that of 1484 patients undergoing allogeneic stem cell transplants over an 18-year period, 7 developed neurological complications; 3 had ADEM and 4 had an inflammatory neuropathy. Those with ADEM each showed inflammation within the brain and spinal cord; biopsy in 2 cases showed demyelination with a heavy macrophage infiltration, although a less evident perivasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In these cases, treatment with steroids and immunosuppression led to neurological improvement and stabilisation in 3 of a series of 4 cases. 7 A recent study from Memorial Sloan Kettering 8 showed that of 1484 patients undergoing allogeneic stem cell transplants over an 18-year period, 7 developed neurological complications; 3 had ADEM and 4 had an inflammatory neuropathy. Those with ADEM each showed inflammation within the brain and spinal cord; biopsy in 2 cases showed demyelination with a heavy macrophage infiltration, although a less evident perivasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Allogeneic bone marrow transplantation (allo-BMT) after myeloablative conditioning is a current, effective treatment for many hematologic malignancies. In post-transplant patients, neurologic complications, which include posterior reversible encephalopathy, seizures, encephalopathy, polyneuropathy and central nervous system (CNS) infections, are described, but CNS immune-mediated demyelinating diseases (IMDD), either primary 4 or secondary to chronic GvHD, 5 are rare. We report on a patient who developed AQP-4-IgG-associated ON, after allo-BMT for AML.…”
mentioning
confidence: 99%
“…The frequency of post-allo-BMT IMDD, which include ON, is rare, 0.5%, in the largest series of patients reported so far. 4 Six of the seven patients were transplanted from HLA-matched related donors, and the median time from transplant to the onset of neurologic symptoms was 4 months. 4 In another retrospective study on patients with severe autoimmune diseases, IMDD occurred up to 5 years after allo-BMT.…”
mentioning
confidence: 99%
See 2 more Smart Citations